2012
DOI: 10.1155/2012/752015
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity ofLactobacilluson Carrageenan-Induced Paw Edema in Male Wistar Rats

Abstract: Introduction. Lactobacillus casei and Lactobacillus acidophilus were used to assess the anti-inflammatory properties in carrageenan induced acute inflammatory model. Materials and Methods. Diclofenac sodium was used as standard drug at concentration of 150 mg/kg of body weight. Culture of Lactobacillus  2 × 107 CFU/ml was given orally. Edema was induced with 1% carrageenan to all the groups after one hour of the oral treatments. Paw thickness was checked at t = 1, 2, 3, 4, 5, and 24 hours. Stair climbing score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 33 publications
4
107
0
3
Order By: Relevance
“…Carrageenan-induced hind paw edema acute inflammation test model is biphasic. First phase starts with the release of histamine, serotonin, and kinins, while the second phase is related to the release of prostaglandins like substances [25]. All of the tested Scorzonera extracts were found be inactive in serotonin-induced hind paw edema model [23].…”
Section: Resultsmentioning
confidence: 94%
“…Carrageenan-induced hind paw edema acute inflammation test model is biphasic. First phase starts with the release of histamine, serotonin, and kinins, while the second phase is related to the release of prostaglandins like substances [25]. All of the tested Scorzonera extracts were found be inactive in serotonin-induced hind paw edema model [23].…”
Section: Resultsmentioning
confidence: 94%
“…Lactobacillus and its important species, such as L. casei and Lactobacillus acidophilus, have been used against many pathological and disease conditions. 31 Lactobacillus has been assessed for its immune-modulatory properties in various experiments. 31,32 In an ovariectomized (Ovx) mouse menopausal model, Britton et al found that Lactobacillus reuteri treatment significantly protected Ovx mice from bone loss.…”
mentioning
confidence: 99%
“…Probiotics have recently emerged as the most powerful food grade microbial agents comprise the ability to express numerous health promoting functions of considerable commercial value and therapeutic potential. These are live microorganisms, when administered in adequate amounts confer several health benefits on the host [1], which includes improving cholesterol assimilation [2], lactose tolerance [3], anti-inflammatory [4], antioxidative [5], anticancer [6], antidiarrheal [7], antiallergic [8], antidiabetic [9], antihypertensive effects [10], controlling obesity [11], and also helps in mineral absorption [12]. Probiotics received generally-regarded-as-safe status, due to its safety profile.…”
Section: Introductionmentioning
confidence: 99%